Flight of the diamond smugglers : a tale of pigeons, obsession, and greed along coastal South Africa - Frank, Matthew Gavin (Liveright Publishing Corporation, 2021)
"Blending elements of reportage, memoir, and incantation, Flight of the Diamond Smugglers is a stunning investigation into the role of carrier pigeons in South African diamond smuggling. Nearly every town along South Africa's infamous diamond coast has been deemed "overmined." Before the area fully becomes a series of abandoned outposts, journalist Matthew Gavin Frank drives from Oranjemund, Namibia to the De Beers mining towns of Alexander Bay, Porth Nolloth, and Kleinzee. What begins as an attempt to peer behind the curtain cloaking the global diamond trade soon becomes a tale of obsession, as Frank learns about the various and ingenious methods used in illicit diamond smuggling-particularly, the sneaking of carrier pigeons onto mine property, affixing diamonds to them, and sending them into the air to fly home. So rampant is this method that a law in 1998 made it illegal to not shoot a pigeon on sight. Frank juxtaposes the endangered lives of local diamond diggers (whose average lifespan is 37 years) who raise pigeons in secret with the corporate boardrooms of De Beers, while also synthesizing myths across histories and cultures in which diamonds and gems intersect. As he speaks with miners, former heads of security, environmental managers, and more, he gets ever-closer to the elusive Mr. Lester-a tall-tale villain meant to frighten would-be smugglers, and the only person who can answer Frank's questions, if he is indeed real. Written in atmospheric and lyrical prose, Flight of the Diamond Smugglers becomes an urgent portrait of labor, greed, and our penchant for ownership"--